Soccer and volleyball players do not land differently: implications for anterior cruciate ligament injury risk - Brunetti, C.; Rabello, R.; Poletti, N.; Silva Zandonato, L.; Ranzini, A.; Bertozzi, F.; Sforza, C. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Non-contact anterior cruciate ligament injuries are common in soccer and volleyball, occurring during changes of direction and landings. This study aimed to investigate kinematic differences between soccer and volleyball players in single-planar and multiplanar landing tasks, simulating sport-specific injury mechanisms. Since the anterior cruciate ligament injury rate in soccer is higher than in volleyball, we hypothesized that volleyball players would adopt safer landing strategies, especially in single-planar landing tasks. METHODS: Twenty-two soccer and 19 volleyball players performed single-leg drop landing, drop jump in vertical, 45°-medial and 45°-lateral directions. Box height and jump length were adapted to the subject`s height and performance level, respectively. A 9-camera motion capture system provided lower limb kinematics. Two mixed multivariate analyses of covariance (sport, task, sex as covariate) were used to compare soccer and volleyball players` initial contact and peak kinematics (a=0.05). RESULTS: Task had significant effects on lower limb initial contact and peak angles, as expected. Sport and task × sport interaction had no significant effects on kinematics. CONCLUSIONS: Soccer and volleyball players` landing strategies were thus similar in each task, in opposition to initial hypotheses. We might speculate that the higher anterior cruciate ligament injury rate in soccer may be more related to non-predictable factors than the isolated landing kinematics.